Kinetic Theory in the Earth Sciences - Lasaga, A. C. (Antonio C.) (Book collections on Project MUSE., 1998)
The Earth is shaped by processes as fleeting as molecular motion and as slow as the movement of tectonic plates. This landmark book is the first comprehensive treatment of the huge range of kinetic processes that lie along the continuum from one of these extremes to the other. A leading researcher in modern geochemistry and geophysics, Antonio Lasaga reviews the theories and quantitative tools that explain these processes, and he shows how they can be applied in the field and laboratory. Chapters focus on such theoretical topics as rate laws of chemical reactions, transport theory, diffusion, irreversible thermodynamics, nucleation theory, and the theory of crystal growth and dissolution. These theories help to explain such kinetic processes as molecular complexation, fluid flow, weathering, oxidation, nucleation, growth, magma generation, biological membrane reactions, atmospheric gas reactions, geochemical cycles, mantle creep, subduction, and erosion. Throughout, Lasaga emphasizes the need to view earth-science phenomena as ongoing processes--to add fully the element of time to models of earth dynamics. He draws on extensive knowledge of geology, chemistry, physics, and mathematics and makes creative use of numerous examples from both nature and the laboratory. Kinetic Theory in the Earth Sciences will be essential reading for geologists and chemists who wish to understand the application of chemical kinetics to the workings of the Earth. Originally published in 1998. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.